Annuals naturally at home in the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The flat, sandy landscape of the Sahel is the last place one would expect to find a green revolution taking place. 'Yet, a revolution of a sort has quietly taken place in the Sahelian flora that contradicts observations in other arid and semi-arid...